THE DEVELOPMENT OF LEARNER-CENTERED MATHEMATICS CURRICULUM FOR CULTIVATING MATHEMATICAL PROBLEM-SOLVING SKILLS IN PRIMARY SCHOOL STUDENTS - Lyu, Dongmei; Dudsdeemaytha, Jitra; Yoonisil, Waiyawut (วารสาร มจร พุทธปัญญาปริทรรศน์, 2025)
This article aimed to study (1)The current situation of mathematical problem-solving skills in primary school students; (2)The development of learner-centered mathematics curriculum for cultivating mathematical problem-solving skills in primary school students; (3)The effectiveness of the learner-centered mathematics curriculum for cultivating mathematical problem-solving skills in primary school students. The sample was one classroom (40 students) of fourth-grade students studying in the 2023-2024 academic year of Zhoukou City first primary school located in Henan province in China. They was selected by multi-stage sampling method, the instrument for collecting data was the mathematical problem-solving skills test paper. The researcher reviewed the literature on studies on elementary school students’ mathematical problem solving skills, learner-centered approach theories including cooperative learning, problem-based learning and gamification, curriculum development and design theories, and combined the results of interviews with teachers and students to design the learner-centered mathematics curriculum. Descriptive statistics and content analysis were used to analyze the data. The research results were found as follows: 1) The results showed that the country attaches great importance to cultivating pupils’ problem-solving skills. However, current research shows that primary school students have a series of problems in mathematical problem-solving skills, such as weak grasp of basic knowledge, lack of independent thinking and innovation awareness, and insufficient practical operation opportunities. From the perspective of teachers, They are insufficient in cultivating pupils’ mathematical problem-solving skills, and there are some problems as follows: outdated teaching concepts, traditional teaching methods, neglect of students’ individual differences, undiversified student evaluation methods, and so on. 2) This study integrates three learner-centered teaching techniques, including cooperative learning, problem learning and gamification, to design diverse activities and encourage students to actively explore and solve problems.The learner-centered mathematics curriculum consists of six components: curriculum principles, curriculum objectives, curriculum content, teaching method, instructional materials and learning evaluation. 3) The learner-centered mathematics curriculum for cultivating mathematical problem-solving skills in primary school students is effective.